PENGARUH ROLE STRESSORS PADA BURNOUT AUDITOR DENGAN KECERDASAN EMOSIONAL SEBAGAI VARIABEL PEMODERASI (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK SE-PROVINSI BALI) - Wiryathi, Ni Made; Rasmini, Ni Ketut; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
Burnout is a representation of specific psicologycal stress syndrome which is a negative response that arises as a result of work pressure. The antecedents of burnout are role stressors which consist of role conflict, role ambiguity, and role overload. Previous researchs of the relationship between role conflict, role ambiguity, and role overload with burnout have found inconsistent results. This research was conducted in 2013 and directed to determine the ability of emotional intelligence in moderates the effect of role conflict, role ambiguity, and role overload on auditor's burnout in all public accounting firm in Bali. Samples were taken with a saturated sample method. Data collection was done using questionnaires and dedicated to 105 auditors. The analysis technique used in this study is Moderated Regression Analysis. The instruments have been examined for its validity and reliability. The model also has passed the classical assumptions of regression analysis. Statistical analysis showed that emotional intelligence moderates the influence of role conflict, role ambiguity, and role overload on burnout experienced by auditor at public accounting firm in Bali Province. Statistical tests showed that emotional intelligence is weaken the influence of role conflict, role ambiguity, and role overload on burnout experienced by auditor at public accounting firm in Bali Province. This means that the higher role conflict, role ambiguity, and role overload experienced by auditor at public accounting firm in Bali province, the higher the likelihood of burnout, the auditors who have low emotional intelligence.
Keywords: Burnout, Role Stressors, Role Conflict, Role Ambiguity, Role Overload, Emotional Intelligence, Auditor, Public Accounting Firm in Bali